2008
DOI: 10.1016/j.actatropica.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Rattus norvegicus as a model for persistent renal colonization by pathogenic Leptospira interrogans

Abstract: Leptospirosis continues to be a disease with a poorly understood pathogenesis. The experimental rat model is amenable for the investigation of leptospiral dissemination, tropism, persistence of renal colonization and factors related to disease resistance. In this study, Wistar rats were infected intraperitoneally with virulent Leptospira interrogans serovar Copenhageni strain Fiocruz L1-130. The detection of leptospires in tissue samples was based on culture, silver staining and immunofluorescence techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
119
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 25 publications
16
119
2
5
Order By: Relevance
“…This study was able to isolate Leptospira interrogans serovar Copenhageni strain Fiocruz L1-130 (KO et al, 1999), and surveys conducted by KO et al (2007) and by ATHANAZIO et al (2008) emphasizes the important role of rodents in the epidemiological chain of leptospirosis, indicating their condition as reservoir of this strain to humans.…”
Section: Leptospiramentioning
confidence: 93%
See 1 more Smart Citation
“…This study was able to isolate Leptospira interrogans serovar Copenhageni strain Fiocruz L1-130 (KO et al, 1999), and surveys conducted by KO et al (2007) and by ATHANAZIO et al (2008) emphasizes the important role of rodents in the epidemiological chain of leptospirosis, indicating their condition as reservoir of this strain to humans.…”
Section: Leptospiramentioning
confidence: 93%
“…In rural areas the transmission occurs more frequently because of defi ciency of good sanitary practices in animal handling. Surveys conducted by KO et al (2007) and by ATHANAZIO et al (2008) described the pathogenesis and the pathological changes caused by Leptospira interrogans serovar Copenhageni strain Fiocruz L1-130 (KO et al, 1999 in the kidneys of rats.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of naturally-occurring leptospiral infection in rats has not been extensively studied and is complicated by a wide array of potentially confusing environmental factors that may also induce pathology in wild urban rats (11). The present study evaluated renal pathology in urban rats from a city where the prevalence of leptospiral isolation by kidney culture was approximately 20% (7).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating renal morphology in captured urban rats carrying leptospires have all reported that interstitial nephritis was the principal change attributed to leptospires (9)(10)(11). The pathogenesis of naturally-occurring leptospiral infection in rats has not been extensively studied and is complicated by a wide array of potentially confusing environmental factors that may also induce pathology in wild urban rats (11).…”
Section: Discussionmentioning
confidence: 99%
“…Rats are resistant to acute disease and are more suited to studies focusing on mechanisms of persistent infection (3,13). The mouse model offers a broad array of immunological and genetic tools available for basic research; however, it has been poorly explored in leptospirosis.…”
mentioning
confidence: 99%